PENERAPAN PERKARA PRODEO DI PENGADILAN NEGERI SELONG KLAS I.B - pareski (Fakultas Hukum Universitas Gunung Rinjani, 2024)
The purpose of this study is to find out How is the implementation of Prodeo Cases In The Selong State Court. When filing a lawsuit in court, the requirement to pay down payment through the bank has been stated in Supreme Court Circular Letter Number 04 of 2008 concerning Collection of Case Fees. For those who cannot afford to pay court fees, they can file a case for free (Prodeo) by obtaining permission to be exempt from paying court fees. The Selong District Court is obliged to provide this policy and implement it optimally in providing legal assistance to people who cannot afford it in accordance with what is mandated in the Republic of Indonesia Supreme Court Regulation Number 1 of 2014 concerning Guidelines for Providing Legal Services for Disadvantaged People. In practice, the Prodeo case does not proceed according to the mandate of statutory regulations based on the results of research obtained at the Selong District Court, the process of applying for free legal aid (Prodeo) at the Selong District Court has not been running since 2010 until now, because there are no individual members of the community who resolved the matter through Prodeo.